Cost Estimation Performance in the Construction Projects: A Systematic Review and Future Directions - Mohammad Waffy, Fazil; Lee, Chia Kuang; Puteri Fadzline, Muhamad Tamyez (Penerbit Universiti Malaysia Pahang, 2021)
Cost estimation in construction project is very critical for avoiding cost overrun in the project. This paper aims to provide a basis for improving cost estimation performance in construction through a systematic review of previous studies for last 31 years. The papers have identified a total of 238 construction cost estimation papers in 23 journals. Only 33 papers focused on factors influencing the performance of cost estimation. These papers were then analyzed, synthesized, and summarized in terms of the distribution across countries and citation influences. The factors of cost estimation performance were clustered to several themes with most of the factors in control themes. The factors in control themes are cluttered based on Organizational Control Theory (OCT). However, control themes provide less conceptual basis and dynamic to explain cost estimation performance and relationship among the factors. Therefore, this study reclassified other factors of cost estimation performance with reference to Contingency Theory (CT) and Task-Technology Fit Theory (TTFT). Hence, a new framework with relationship among the factors and cost estimation performance was developed. Further development and research of using the CT and TTFT frameworks were also discussed.